Teaching Mathematics in the Artificial Intelligence Era: Challenges and Concerns in Higher Education - Panaoura, Rita (Social Education Research, 2025)
Problem-solving has been at the core of mathematical education for decades. However, the objectives set for understanding mathematical concepts and developing problem-solving strategies within a realistic and interdisciplinary framework have not been achieved to the expected extent. Over the past decade, the need for persistence in mathematical problem-solving has been emphasized as a process of self-regulation in cognitive behaviour, helping learners overcome obstacles that require flexibility and adaptive actions. Learners often seek external assistance when facing difficulties in solving mathematical problems. Recently it seems that at the secondary and higher education levels, artificial intelligence has taken on this role. Research findings highlight students' willingness and expectation to acquire the necessary knowledge and skills to utilize Artificial Intelligence (AI) tools for learning, developing strategies, and enhancing problem-solving abilities to become more proficient problem solvers. We must acknowledge the advancements in AI and leverage its capabilities in an ethical and effective manner, including adaptive assessment and self-assessment tools, immediate feedback, identification of errors in mathematical thinking, and suggestions for alternative courses of action. The use of appropriate AI tools by cognitively mature individuals can positively contribute to the development of metacognitive skills that improve mathematical ability. The effective use presupposes the relevant teachers' knowledge, skills and high self-efficacy beliefs about the use of AI tools either in teaching or in learning. We present a position paper on the issue and we discuss our main concerns we have to take into consideration, under a pedagogical perspective and the challenges we have to face the following up years.